2018
DOI: 10.1038/s41423-018-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

The cellular metabolic landscape in the tumor milieu regulates the activity of myeloid infiltrates

Abstract: Malignant cells upregulate distinct energy metabolism programs that support their proliferation, migration, and adaptation to the stressful tumor microenvironment (TME). Additionally, this exaggerated metabolic activity allows cancer cells to hijack essential nutrients and outcompete neighboring infiltrating immune cells, thereby impairing antitumor immunity. During recent years, there has been great interest in the field to understand the tumor-induced energy metabolism signals that regulate the function of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 122 publications
0
25
1
Order By: Relevance
“…Hasmim et al (15) demonstrated the weak expression of SCIN in 9 out of 83 patients with head and neck cancer, indicating that the role of SCIN may vary within different types of tumor. This paradoxical function of SCIN in different types of cancer may be attributed to different genetic backgrounds and distinct tumor milieu(22). However, the present study demonstrated that SCIN was tumor suppressive in HCC.…”
contrasting
confidence: 58%
“…Hasmim et al (15) demonstrated the weak expression of SCIN in 9 out of 83 patients with head and neck cancer, indicating that the role of SCIN may vary within different types of tumor. This paradoxical function of SCIN in different types of cancer may be attributed to different genetic backgrounds and distinct tumor milieu(22). However, the present study demonstrated that SCIN was tumor suppressive in HCC.…”
contrasting
confidence: 58%
“…Moreover glycolysis, the metabolic pathway preferred by TIMs and tumor cells during the elimination phase, mediates production of proteins, nucleic acids, lipids, lactate, adenosine, and consequently immunosuppressive acidification of the TME. As a result TIMs undergo peroxisome proliferator-activated receptor gamma (PPARγ) and STAT-mediated metabolic reprogramming ( 61 ). They switch from glycolysis to oxidative phosphorylation and lipid catabolism (fatty acid oxidation).…”
Section: Myeloid Cells Have a Cat And Mouse Relationship With Cancer mentioning
confidence: 99%
“…Accordingly, there has been a surge of interest in defining the mechanisms by which aberrant immune cell metabolism impacts cancer progression and therapeutic outcomes. In this issue, Rodriguez and Peng discuss the latest research advances in cancer immunometabolism and how novel insights can be harnessed to treat cancer 7,8 . Myeloid cells contribute to the suppressive intratumoral environment and may directly promote human tumor stemness 9 .…”
mentioning
confidence: 99%
“…Myeloid cells contribute to the suppressive intratumoral environment and may directly promote human tumor stemness 9 . Tumorinfiltrating myeloid cells are the subject of a review by Rodriguez 7 . These heterogeneous and developmentally immature myeloid cells are responsive to dysfunctional metabolism such as poor glycolysis and enhanced lipid metabolism and the associated metabolites, such as adenosine, cAMP, IDO, lactate, succinate, PGE2, fatty acid, lipoproteins, and oxidized forms that may promote their intratumoral accumulation and suppressive effects on T cells 7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation